2022
DOI: 10.3389/fmed.2021.836528
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidins Exert a Radioprotective Effect on the Testes and Intestines Through Antioxidant Effects and Inhibition of MAPK Signal Pathways

Abstract: The testes and intestines are highly sensitive to ionizing radiation. Low-dose radiation can cause infertility and enteritis. However, there is a lack of safe and efficient radioprotective agents. This study aims to investigate the radioprotective effects of grape seed proanthocyanidins (GSPs) on testicular and intestinal damage induced by ionizing radiation. In vitro, GSPs reduced the apoptosis and proliferation inhibition of mouse testicular stromal cells TM3 and human small intestinal crypt epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Mammalian spermatogenesis is a complex process, which proceeds through a welldefined order including the mitotic expansions of spermatogonia, the meiotic reduction divisions of spermatocytes, and spermiogenesis [34,35]. The total duration cycle of bull spermatogenesis is 61 days [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian spermatogenesis is a complex process, which proceeds through a welldefined order including the mitotic expansions of spermatogonia, the meiotic reduction divisions of spermatocytes, and spermiogenesis [34,35]. The total duration cycle of bull spermatogenesis is 61 days [36].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the sperm content of MDA was significantly reduced in the 30, 40, 50, 60 µg/mL GSPs compared with the control in frozen-thawed semen. Several studies have shown that GSPs inhibit oxidative stress damage through the activation of mitogen-activated protein kinases (MAPKs) and NF-κB signaling [35], while mammalian target of rapamycin (mTOR) is necessary for both the proliferation and differentiation of progenitor spermatogonia during spermatogenesis [44,45]. A previous study indicated that GSPs can improve chemotherapy drug cisplatin (CIS)-induced testicular cell apoptosis via activating the phosphatidylinositol 3-kinase (PI3K)/V-akt murine thymoma viral oncogene homolog (Akt)/mTOR signaling pathway [46].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is the result of an overload of free radicals relative to the body's IOP Publishing doi:10.1088/1755-1315/1262/7/072039 2 antioxidant defences [5], with the free radicals wreaking havoc on cells and damaging biological molecules like DNA, proteins, and lipids [6]. Proanthocyanidins were found to have strong antioxidant properties, protecting sperm cells from radiation damage and altering gene expression among other things [7]. The stress hormone corticosterone is regulated by proanthocyanidins [9], and proanthocyanidins themselves decrease programmed death [8].Given the foregoing, this study set out to determine whether or not proanthocyanidins may boost immunity by acting as a natural antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Because free radicals can damage any biological molecule, including DNA, proteins, and lipids, when their production outpaces that of antioxidants, oxidative stress [5] ensues, which in turn increases the risk of cell damage and the IOP Publishing doi:10.1088/1755-1315/1262/7/072040 2 occurrence of pathological complications [6]. Protecting sperm cells from radiation damage and influencing gene expression [7] are just two examples of the ways in which proanthocyanidins have been shown to exhibit powerful antioxidant action. Proanthocyanidins inhibit apoptosis [8] and control corticosterone release in times of stress [9].…”
Section: Introductionmentioning
confidence: 99%